Preparation and optimization of a soft magnetic brake friction material based on permalloy additive. Issue 2 (1st February 2021) - Wang, Xiaoyang; Bao, Jiusheng; Liu, Jinge; Yin, Yan; Liu, Tonggang; Zhao, Shaodi
Abstract : Purpose: This paper aims to develop of magnetic field controlled friction braking technology, a novel brake friction material with magnetic was designed and prepared in this paper. Design/methodology/approach: The permalloy, a soft magnetic material, was selected as an additive to design and prepare the magnetic brake material. The friction, wear performance and permeability of each brake pads were investigated by experiments. By choosing the performance of friction coefficient fluctuation, friction coefficient deviation and mean wear rate as optimization parameters, the formulation of the magnetic friction material was optimized based on Fuzzy theory by using analytic hierarchy process methods and SPSS software. Findings: The results showed that the developed soft magnetic friction material has not only superior friction coefficient, permeability and inferior wear rate but also good physical and mechanical properties. Originality/value: Permalloy powder was added to the formulation of friction material to achieve a new functional friction material with high magnetic permeability. It is believed that this research will be of great theoretical and practical significance to develop both new brake materials and active control technology of the braking process in the future.